Giải các phương trình sau:
a) sin(2x−π6)=−√32
b) cos(3x2+π4)=12
c) sin3x−cos5x=0
d) cos2x=14
e) sinx−√3cosx=0
f) sinx+cosx=0
Sử dụng các công thức nghiệm của phương trình lượng giác
a)
sin(2x−π6)=−√32⇔sin(2x−π6)=sin(−π3)
Advertisements (Quảng cáo)
⇔[2x−π6=−π3+k2π2x−π6=π+π3+k2π(k∈Z)⇔[2x=−π6+k2π2x=3π2+k2π(k∈Z)⇔[x=−π12+kπx=3π4+kπ(k∈Z)
b) cos(3x2+π4)=12⇔cos(3x2+π4)=cosπ3
⇔[3x2+π4=π3+k2π3x2+π4=−π3+k2π(k∈Z)⇔[x=π18+k4π3x=−7π18+k4π3(k∈Z)
c)
sin3x−cos5x=0⇔sin3x=cos5x⇔cos5x=cos(π2−3x)⇔[5x=π2−3x+k2π5x=−(π2−3x)+k2π⇔[8x=π2+k2π2x=−π2+k2π⇔[x=π16+kπ4x=−π4+kπ
d)
cos2x=14⇔[cosx=12cosx=−12⇔[cosx=cosπ3cosx=cos2π3⇔[[x=π3+k2πx=−π3+k2π[x=2π3+k2πx=−2π3+k2π
e)
sinx−√3cosx=0⇔12sinx−√32cosx=0⇔cosπ3.sinx−sinπ3.cosx=0⇔sin(x−π3)=0⇔sin(x−π3)=sin0⇔x−π3=kπ;k∈Z⇔x=π3+kπ;k∈Z
f)
sinx+cosx=0⇔√22sinx+√22cosx=0⇔cosπ4.sinx+sinπ4.cosx=0⇔sin(x+π4)=0⇔sin(x+π4)=sin0⇔x+π4=kπ;k∈Z⇔x=−π4+kπ;k∈Z